Homeopathic treatment of COVID-19 caused by novel coronavirus SARS CoV2-a real-world experience - Arora, Geeta Rani; Indani, Ashish; Goyal, Arti; Bhutada, Poonam (International Journal of Advances in Medicine, 2022)
Background: The unprecedented healthcare challenge of COVID-19 uncovered a new set of challenges for therapy and management of infective conditions. The aim of the study was to established efficacy and safety homoeopathic medicines, which works on principles of similar symptomatology of the disease and the drug, individualization of therapy and hyper-attenuated prescriptions. Methods: The present study was a single centre, OPD based, prospective real-world, all-comer study that included 94 patients of COVID-19, diagnosed based on criteria advised by the Ministry of AYUSH). Results: In all, 94 all-comer, real-world patients of COVID-19 were included in the study, diagnosed on this basis of the MoH guidance criteria. All patients were symptomatic. The overall age of the patients was 40.98 ±19.98 years. Few patients [n=21 (16.84)] had comorbidities while a majority of patients [n=79 (83.16%)] had no notable comorbidity. All the patients were relieved to be asymptomatic in maximum 6 days. In the reversed calculation of Cohen’s D, indicated that the effect of therapy was significantly large. However, pertaining to the data volume, the effect size was not statistically significant. Conclusions: Individualized homeopathic medicine were effective in treatment of COVID-19. However, Bryonia alba and arsenic album were most commonly indicated medicines p overall <0.0001 (Chi square for equal distribution of top 10). Another trend observation established that Bryonia alba was most commonly indicated and effective medicine; hence a potential homeopathic medicine for epidemic (genus: Epidemicus).